2021
DOI: 10.3390/ijms22052304
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Role of Plasminogen in Cancer

Abstract: Fibrinolytic factors like plasminogen, tissue-type plasminogen activator (tPA), and urokinase plasminogen activator (uPA) dissolve clots. Though mere extracellular-matrix-degrading enzymes, fibrinolytic factors interfere with many processes during primary cancer growth and metastasis. Their many receptors give them access to cellular functions that tumor cells have widely exploited to promote tumor cell survival, growth, and metastatic abilities. They give cancer cells tools to ensure their own survival by int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 55 publications
(74 reference statements)
0
15
0
Order By: Relevance
“…Congenital plasminogen deficiency is a rare genetic disorder caused by an alteration in the PLG gene. Plasminogen activation plays an important role in the invasion and metastasis of lung, breast and brain cancer [ 41 , 44 , 45 ]. To determine the physical relationship between Chi3L1 and PLG, immunoprecipitation was performed using the anti‐Myc antibody.…”
Section: Resultsmentioning
confidence: 99%
“…Congenital plasminogen deficiency is a rare genetic disorder caused by an alteration in the PLG gene. Plasminogen activation plays an important role in the invasion and metastasis of lung, breast and brain cancer [ 41 , 44 , 45 ]. To determine the physical relationship between Chi3L1 and PLG, immunoprecipitation was performed using the anti‐Myc antibody.…”
Section: Resultsmentioning
confidence: 99%
“…PLG, a 92-94-kilodalton protein produced in the liver and circulated in the blood, is known to be involved in the degradation of extracellular matrix, cell migration, angiogenesis, oncogenesis, and metastasis (20,21). The PLG is associated autophagy of cancer (22). Fang et al demonstrated that Plasminogen kringle 5 suppressed the growth gastric cancer by inhibiting angiogenesis and apoptosis (23).…”
Section: Discussionmentioning
confidence: 99%
“…ECM remodeling is influenced by proteinases, MMPs and PA–plasmin systems [ 100 , 101 ]. Plasmin, either directly or indirectly through MMPs, degrades components of the ECM, thus contributing to cancer cell invasion and metastases [ 102 ]. It is reported that MMPs are secreted and activated primarily by tumor cells but also by cellular components of the TME [ 103 ].…”
Section: Notch Signaling Regulates Bc Progressionmentioning
confidence: 99%